Exploration Of The 2021 Senja Drive-In Visitor Experience Using The Event Experience Conceptual Model - Wera, Inrid Agelia Floriana; Ainun, Lutfiah Nur; Suroto, Peni Zulandari; Handoko, Rudi; Dewantara, Made Handijaya (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
Drive-in Events are a new phenomenon in the event industry in 2020, emerging as innovations to overcome social distancing policies. The researcher was interested in exploring the experience of Drive-In Senja 2021 visitors using the event experience conceptual model, which helps add to the study of event experience and provides insight for the event industry in designing event experiences, especially Drive-In event experiences. This study uses the conceptual basis of the event experience conceptual model. Qualitative approaches and phenomenological methodologies, especially IPA (interpretative phenomenology analysis), were used to examine five informants representing three categories: couple, double date, and girls' night out. The results of data analysis found 37 emergent themes that formed 11 superordinate themes, which constructed the Drive-In Senja event experience conceptual model. The Drive-In Senja event experience conceptual model differs from the event experience conceptual model, namely a personal and social realms in a more detailed event environment. As a result, there are more superordinates in the personal realm than in the event environment, which shows the limitations of Drive-In Senja organizers in designing event environments during pandemic conditions.